Cathode with disordered rocksalt material and method of forming the cathode
Patent Information
- Application Number
- JP2024223882
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-08-18
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2041-08-17
Smart Images

Figure 2025028307000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention is in the field of battery technology. [Background technology]
[0002] Lithium metal oxides have been used to formulate cathode materials for lithium ion batteries. Cathodes are derived from several basic crystal structure types, such as spinel, olivine, and layered oxide structures. Layered oxide structures include lithium-rich structures where additional lithium is present in the structure.
[0003] In recent years, much attention has focused on disordered rock-salt structures, such as those formed from certain lithium metal oxides. xLi3NbO4·(1-x)LiMO2(1) Compounds represented by the formula (1), where M is a divalent or trivalent cation, have been shown to be a promising class of transition metal oxides for use as cathodes in lithium ion batteries. Compounds of formula (1) are considered disordered rock salts in which random atomic arrangements of lithium and transition metal ions are packed in a close-packed cubic structure. These disordered rock salt type compositions offer the ability to contain up to three lithium atoms per formula unit, which is more than conventional lithium-rich layered materials. Formula (1) represents the Li x M y N z O w It can be expressed by modifying it as follows.
[0004] Disordered rock-salt structures are attractive cathode materials for next-generation lithium-ion batteries because of their higher specific energy density (e.g., higher theoretical energy density) than state-of-the-art cathode materials, such as layered lithium metal oxide structures. For example, certain disordered rock-salt structured materials have a theoretical gravimetric energy density of about 1120 Wh / kg, while LiMn2O4 active materials have a theoretical gravimetric energy density of about 492 Wh / kg, and LiMn 1.5 Ni 0.5O4 has a theoretical gravimetric energy density of about 691 Wh / kg. This energy density is particularly attractive when lower cost raw materials, such as manganese, are used as components in the disordered rock-salt structure. Thus, the disordered rock-salt material can achieve a relatively high energy density at a relatively low material cost. To achieve a relatively high energy density, known cathode materials require higher cost raw materials, such as cobalt or nickel.
[0005] A drawback of disordered rock-salt materials is their relatively poor conductivity. One way to improve the conductivity of battery materials is to reduce the particle size in order to shorten the transport paths of electrons and ions. Reducing the particle size can increase the conductivity by shortening the transport paths of electrons and ions. Unfortunately, smaller particle sizes also inherently limit the energy density per volume of the electrode, which reduces the energy density of the battery cell. Thus, at least some of the advantages of the high energy density inherent in disordered rock-salt materials are sacrificed to alleviate the conductivity problem. Summary of the Invention
[0006] In one or more embodiments, a method for forming a cathode is provided that includes milling a suspension of precursors with a micromedia mill to form a mixture of primary particles in the suspension. The precursors include one or more metal compounds. The method includes, after the milling step, spray drying the suspension to form secondary particles. The secondary particles are aggregates of the primary particles. The method further includes annealing the secondary particles to form an irregular rock salt type powder.
[0007] In one or more embodiments, a cathode for a rechargeable battery is provided. The cathode comprises an irregular rock salt type powder characterized by secondary particles having an average particle size of 1 micrometer or more and 20 micrometers or less. Each of the secondary particles is an aggregate of primary particles. The primary particles have an average particle size of 400 nanometers or less.
[0008] In one or more embodiments, a method for forming a lithium ion battery is provided that includes milling a suspension of precursors to form a mixture of primary particles in the suspension. The precursors include one or more metal compounds. The method includes spray drying the suspension after the milling step to form secondary particles. The secondary particles are aggregates of the primary particles. The method includes annealing the secondary particles to form an irregular rock-salt type powder, and milling the irregular rock-salt type powder with one or more carbon precursors after the annealing step. The method further includes mixing the irregular rock-salt type powder with one or more solvents to form a slurry, drying the slurry on a metal current collector to form a composite cathode film, inserting the composite cathode film into a cell casing such that a separator is disposed between the composite cathode film and the anode, and providing an electrolyte into the cell casing. [Brief description of the drawings]
[0009] [Figure 1] 1 is a flowchart of a method for forming a cathode for a lithium ion battery, according to an embodiment. [Diagram 2] 1 is a magnified image of a suspension showing irregular rock-salt type secondary particles after a spray drying process, according to an embodiment. [Diagram 3] 1 is a magnified image of irregular rock-salt type secondary particles after an annealing process, according to an embodiment. [Figure 4] 4 is a magnified image showing an enlarged view of one irregular rock-salt type secondary particle with respect to FIG. 3, according to an embodiment. [Diagram 5]1 is a graph plotting voltage profiles of spherical secondary particles of irregular rock-salt phase powder at discharge rates of 0.1C and 1C. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Detailed Description The following definitions apply to some of the aspects described for some embodiments of the present invention. Similarly, these definitions may be expanded herein. Each term is further explained and illustrated through the description, drawings, and examples. Any interpretation of the terms in this specification should take into account the entire description, drawings, and examples provided herein.
[0011] The singular terms "a," "an," and "the" include the plural unless the context clearly dictates otherwise. Thus, for example, reference to an object can include multiple objects unless the context clearly dictates otherwise.
[0012] The term "transition metal" refers to chemical elements in groups 3 to 12 of the periodic table, including scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), and arsenic (As). h), palladium (Pd), silver (Ag), cadmium (Cd), hafnium (Hf), tantalum (Ta), tungsten (W), rhenium (Re), osmium (Os), iridium (Ir), platinum (Pt), gold (Au), mercury (Hg), rutherfordium (Rf), dubnium (Db), seaborgium (Sg), bohrium (Bh), hassium (Hs), and meitnerium (Mt).
[0013] Rate "C" (depending on the context) refers to either the discharge current as a fraction or multiple of the "1C" current value at which a battery (in a substantially fully charged state) will be substantially fully discharged in 1 hour, or the charge current as a fraction or multiple of the "1C" current value at which a battery (in a substantially fully discharged state) will be substantially fully charged in 1 hour.
[0014] To the extent that particular battery characteristics may vary with temperature, such characteristics are specified at 30° C., unless the context clearly dictates otherwise.
[0015] Ranges provided herein are inclusive of their endpoints: thus, for example, the range 1 to 3 includes the values 1 and 3, as well as any values in between.
[0016] An embodiment of the present subject matter provides disordered rock-salt compositions and forms (e.g., structures) for use in the formulation of electrodes of electrochemical cells. More specifically, the disordered rock-salt materials disclosed herein can be used to form a cathode. An electrochemical cell utilizing the disordered rock-salt materials disclosed herein can be a lithium-ion battery. The lithium-ion battery can be a secondary battery or a rechargeable battery. For example, discharging and recharging of a lithium-ion battery can be accomplished by intercalation and deintercalation of lithium ions into and out of the cathode, respectively. A lithium-ion battery includes an electrolyte formulation having a lithium salt present in a concentration suitable to conduct lithium ions through the electrolyte formulation between the cathode and the anode during discharge and recharge operations.
[0017] In the disordered rock-salt composition, both lithium and transition metals occupy a cubic close-packed lattice of octahedral sites. In the electrochemical reaction, lithium diffusion proceeds by hopping of lithium from one octahedral site to another via intermediate tetrahedral sites. The lithium in the intermediate tetrahedral sites is in an activated state for lithium diffusion. The activated tetrahedral lithium ion shares faces with four octahedral sites: (i) the site previously occupied by the lithium ion itself; (ii) the vacancy into which the lithium ion migrates; and (iii and iv) two sites that may be occupied by lithium, transition metal, or vacancy.
[0018] In order to provide short electron and ion transport paths to provide suitable conductivity without sacrificing electrode energy density, the irregular rock-salt morphology in the cathode described herein includes micro-sized clusters or aggregates of sub-micro-sized particles. Herein, the micro-sized clusters are also referred to as secondary particles. The secondary particles have an average particle size (e.g., diameter) on the micrometer scale, e.g., 1 micrometer to 20 micrometers. The clusters of sub-micro-sized particles form secondary particles. Herein, the sub-micro-sized particles are also referred to as primary particles. The terms "primary" and "secondary" indicate that the primary particles are formed before the secondary particles, and the secondary particles are aggregates of the primary particles. The primary particles have an average particle size (e.g., diameter) on the nanometer scale, e.g., less than 400 nanometers. The sub-micro primary particles of the irregular rock-salt material provide the desired conductivity, and the micro-sized secondary particles of the irregular rock-salt material result in high electrode energy density. Thus, forming a disordered rock-salt morphology having micro-sized aggregates of sub-micron-sized particles provides the high energy density associated with disordered rock-salt materials without compromising conductivity.
[0019] One or more embodiments disclose the synthesis of an irregular rock-salt type cathode active material. The morphology of the active material includes micro-sized spherical secondary particles that are aggregates of smaller primary particles, as described above. The synthesis includes grinding a metal precursor to produce a homogenous mixture of nano-sized precursor particles. The mixture is then spray-dried to produce spherical precursor particles with a controlled particle size. The spray-drying results in micro-sized spherical precursor particles that are clusters or aggregates of the nano-sized precursor particles. The spherical precursor particles are then subjected to annealing that results in an irregular rock-salt type phase. The annealing conditions are selected to maintain the particle morphology such that the resulting irregular rock-salt type phase has micro-sized spherical secondary particles that are aggregates of the smaller primary particles. Experimental testing of embodiments disclosed herein showed good rate capabilities of 272 mAh / g when cycled from 1.5 V to 4.8 V at C / 10, 30° C., and 193 mAh / g when cycled from 1.5 V to 4.8 V at 1C, 30° C.
[0020] Known disordered rock-salt type morphologies lack the spherical, micro-sized secondary particles that are clusters of smaller primary particles according to embodiments described herein. For example, known disordered rock-salt type materials are synthesized by conventional solid-state chemistry and / or molten salt methods that result in large single-crystal and polycrystalline grain sizes. Due in part to the large grains, disordered rock-salt type materials produced by known methods suffer from poor electrical conductivity.
[0021] The irregular rock salt type cathode active material formed by the process described herein and comprising the secondary particle morphology described herein may have various compositions. For example, compositions of a plurality of irregular rock salt type materials are disclosed in U.S. Patent Application Publication No. 15 / 222377 (now U.S. Patent No. 10280092), the entirety of which is incorporated herein by reference. Generally, irregular rock salt type compositions contain lithium, transition metals, and oxygen. One or more of the transition metal or oxygen sites can be doped to improve electrochemical performance. In a non-limiting example, the oxygen site is doped with fluorine. The general formula for doping at the oxygen site is Li x N y M z O 2-a F a (1) wherein 1.0 < x < 1.65; 0.01 < y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.5; N is one of Ti, Ta, Zr, W, Nb, or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. These compositions have shown excellent intrinsic capacity or energy density, e.g., ~350 mAh / g at 55 °C and C / 40, and ~300 mAh / g at 30 °C and C / 15.
[0022] When a > 0, the presence of fluorine dopants at the oxygen sites in the irregular rock salt can improve the electrochemical performance of a lithium ion battery cell. Without being bound by a particular theory or mechanism of action, the anionic substitution of fluorine for oxygen (forming an oxyfluoride) can improve cycle performance by having greater resistance to attack by hydrogen fluoride from the decomposition of the electrolyte at high voltages. Alternatively, the higher ionic nature of the metal-fluorine bond relative to the ionic nature of the metal-oxygen bond can result in less transition metal leaching from the cathode into the electrolyte and further stabilize the structure.
[0023] In a non-limiting example, the disordered rock salt composition may be devoid of niobium. In another non-limiting example, the N and / or M transition metal sites may be doped instead of or in addition to the oxygen sites.
[0024] 1 is a flow chart of a method 100 for forming a cathode for a lithium ion battery, according to an embodiment. The method 100 can be performed by one or more components of a laboratory or industrial facility. The method 100 can be used to produce a disordered rock-salt (DR) active material for a cathode, which provides high energy density and sufficient conductivity. Optionally, the method 100 can include more steps than described herein, fewer steps than described herein, and / or different steps than described herein.
[0025] At 102, the suspension of precursors is milled to form a mixture of primary particles in the suspension. The precursors include metal compounds and are selected based on the desired composition of the DR material. One or more of the precursors are metal oxides, such as Mn2O3, LiOH, Nb2O5. For doping of oxygen sites with fluorine, at least one precursor includes fluorine. Possible fluorine-containing precursors may include LiF, NbF5, and / or the like. In a non-limiting example, the precursors may include one or more of Mn2O3, Li2CO3, LiF, LiOH, Nb2O5, NbF5, and / or the like. The precursors can be mixed in stoichiometric amounts in deionized water to create the suspension. The milling can be performed by a micro-media mill. The micro-media mill can include concentric cylinders with milling media present in the annular gap between the cylinders. The milling media mills the precursors in the suspension as the cylinders are rotated relative to one another to create small nano-sized primary particles. The micro-media mill can also be designed to form homogeneously sized particles, such that all of the primary precursor particles have approximately the same size within the designed range. The primary particles exiting the mill can have an average particle size of 400 nanometers (nm) or less. Optionally, the average particle size can be 200 nm or less, 100 nm or less, or less. For example, the average particle size can be 50 nm or less, 40 nm or less, 30 nm or less, 20 nm or less, or a similar size or less. In a non-limiting example, the micro-media mill is a laboratory bead mill, such as the Buhler PML2 product, a trademark of the Buhler Group.
[0026] At 104, after grinding of the suspension, the suspension containing the mixture of nano-sized precursor particles is spray-dried to form secondary particles. The step of spray-drying the suspension includes expelling the suspension through a nozzle at high pressure, which causes the suspension to form an aerosol. In a non-limiting example, the spray-drying can be performed using a miniature spray dryer, such as a Buchi B-290 model, a trademark of Buchi. Each drop of the aerosol contains a solvent, such as water, along with small primary particles. As the aerosol dries rapidly, the solvent evaporates and the primary particles coalesce to form secondary particles. The secondary precursor particles are clusters or aggregates of the primary particles. The small, relatively uniform size profile of the primary particles in the aerosol allows the primary particles to aggregate during the drying process. In some embodiments, the spray-drying causes the secondary particles to have a spherical shape. For example, the secondary particles are approximately spherical and can be seen as spherical when viewed through a microscope.
[0027] 2 is a magnified image 200 of a suspension showing DR secondary particles 202 after a spray drying process, according to an embodiment. The image is magnified to the micrometer scale and includes an indicator 204 representing 10 micrometers (μm). As shown in FIG. 2, the secondary particles 202 are spherical in shape and have a size between about 1 μm and about 10 μm. Optionally, some of the secondary particles 202 may be larger than those shown in FIG. 2, for example having a diameter of about 20 μm, while other secondary particles 202 may be slightly smaller than 1 μm, for example 0.5 μm.
[0028] Returning now to method 100, after the spray drying step, the secondary particles are annealed at 106 to form a DR phase powder. The relatively high temperature exposure causes the precursors in the secondary particles to react to form a unitary phase. Although the phases are formed at the elemental level, the conditions of the annealing step are selected to maintain the morphology during firing. For example, the resulting DR phase powder maintains micro-sized spherical secondary particles. Annealing conditions can include heating the particles at temperatures between 750°C and 900°C for a period of 6 hours to 24 hours. Annealing at temperatures outside the specified ranges for periods longer or shorter than the specified periods may cause the secondary particles to bond or fuse into larger structures, which significantly reduces the conductivity of the resulting DR phase. Additionally, the annealing step can be performed under a flow of argon gas. Alternatively, the annealing environment can be nitrogen gas or air instead of argon gas. In other embodiments, the annealing conditions can be selected based on the composition of the disordered rock salt precursor, such as the metals present. For example, a manganese-based composition may utilize the above conditions (e.g., 750-900°C for 6-24 hours), while a composition based on another metal may have a wider temperature range, a higher or lower range, and / or a wider, longer or shorter period of time. In a non-limiting example, the temperature range may be 500°C to 1200°C for a period of 3 hours to 48 hours.
[0029] Figure 3 is a magnified image 300 of secondary particles 202 of DR phase powder 302 after an annealing step. The scale of image 300 is slightly smaller than the scale of image 200 shown in Figure 2. For example, indicator 304 representing 10 μm is slightly shorter than the length of indicator 204 in Figure 2. The fired secondary particles 202 in Figure 3 look slightly different than the unfired particles 202 in Figure 2, but maintain the same shape and size.
[0030] 4 is a magnified image 400 showing a magnified view of one secondary particle 202 of the DR phase powder 302, according to one embodiment. The indicator 404 represents a length of 5 μm. As shown in FIG. 4, the secondary particle 202 has a size (e.g., diameter) of approximately 10 μm. The surface of the particle 202 is a patchwork of small irregularities 402, which represent nano-sized primary particles that have aggregated to form the secondary particle 202.
[0031] In an alternative embodiment, instead of milling and spray drying the lithium-containing precursor with other precursors, the lithium source can be kept separate until the annealing step. For example, spherical secondary particles can be produced as described above, except that they are devoid of lithium. At 106, a lithium source, for example Li2CO3, LiOH and / or LiF, can be mixed with the pre-formed secondary particles and annealed to undergo firing with the secondary particles. The secondary particles 202 of the DR phase powder 302 shown in Figures 3 and 4 can be the same or similar regardless of whether lithium is present in the milling step at 102 or not until the annealing step at 106.
[0032] In another alternative embodiment, the DR phase can be formed before the milling step. For example, the DR phase can be formed by solid-state chemistry methods, such as by solid-state redox reactions of oxide ions. At 102, the formed DR phase, but not the precursor, is milled to form a suspension of primary particles. Then, at 104, the suspension of preformed primary particles of the DR phase is spray-dried to form secondary particles. Because the DR phase is preformed, the annealing step at 106 may have reduced conditions, such as lower temperatures and / or shorter durations, or may be omitted entirely in this embodiment, relative to the previously described embodiment, for example. Alternatively, the annealing step at 106 may not be changed from the previously described embodiment.
[0033] Returning to method 100 of FIG. 1, after the annealing step, the DR phase powder is milled with one or more carbon precursors at 108. Milling with the carbon precursors can form a carbon coating on the secondary particles. The one or more carbon precursors can include acetylene black, carbon black, carbon fiber, graphite, carbon nanotubes, KJ600, and / or the like. In an embodiment, the one or more carbon precursors are milled in a ratio where the irregular rock salt type powder represents a majority and the carbon precursor represents a minority. For example, the ratio can be 60:40, 70:30, 80:20, or 90:10 DR phase powder:carbon precursor. In a non-limiting example used in experimental testing, the ratio is 80:20 DR phase powder:carbon precursor.
[0034] At 110, the DR phase powder is mixed with one or more solvents to form a slurry. Non-limiting examples of the one or more solvents include poly(vinylidene fluoride) and 1-methyl-2-pyrrolidinone. At 112, the resulting slurry is deposited onto a metal current collector. The metal current collector may be stainless steel. At 114, the slurry is dried on the metal current collector to form a composite cathode film.
[0035] In one embodiment, the cathode membrane produced by the method 100 described above in FIG. 1 has an irregular rock-salt type powder. The irregular rock-salt type powder morphology is characterized by secondary particles having an average particle size of 1 micrometer or more and 20 micrometers or less. Each of the secondary particles is an aggregate of primary particles. The primary particles have an average particle size of 400 nanometers or less.
[0036] The cathode active materials described herein can be utilized in rechargeable lithium ion battery cells. The battery cell includes a cathode and an anode separated by a polymer separator. The battery cell includes an electrolyte that allows for the transport of ions and electrons between the cathode and the anode. The cathode active materials described herein can be used with various types and compositions of anodes and electrolytes.
[0037] In a non-limiting example, rechargeable batteries were formed in a glove box filled with high purity argon (M-Braun, O2 and water content <0.1 ppm). DR composite cathode membrane was used as the cathode. For the anode, thin Li foil was cut to the required size. Each battery cell contained a composite cathode membrane, a polypropylene separator, and a lithium foil anode. The electrolyte contains lithium hexafluorophosphate in a mixture of ethylene carbonate and ethyl methyl carbonate solvents with additives. The battery cells were sealed and cycled from 1.5 V to 4.8 V at 55° C., or in some cases at 30° C.
[0038] FIG. 5 is a graph 500 plotting voltage profiles 502, 504 of spherical secondary particles of DR phase powder at discharge rates of 0.1C and 1C. The voltage profiles 502, 504 show experimental data measured when the battery cell described above was cycled at 30° C. from 1.5V to 4.8V. Profile 502 represents a discharge rate of 0.1C (or C / 10) and profile 504 represents a discharge rate of 1C. FIG. 5 shows that the tested battery cell exhibits a capacity of 272mAh / g at 0.1C (1.5V to 4.8V) and 193mAh / g at 1C. These results show good rate capability with a 1C / 0.1C capacity retention of 71% (e.g., 193mAh / g divided by 272mAh / g).
[0039] In one embodiment, a method for forming a cathode includes pulverizing a suspension of a precursor by a media mill to form a mixture of primary particles in the suspension. The precursor includes one or more metal compounds. The method includes spray drying the suspension after the pulverizing step to form secondary particles. The secondary particles are aggregates of the primary particles. The method further includes annealing the secondary particles to form an irregular rock salt-type powder.
[0040] Optionally, the spray drying step forms secondary particles having an average particle size of 1 micrometer or more and 20 micrometers or less. The pulverizing step can form a mixture of primary particles such that the primary particles have an average particle size of 400 nanometers or less. Optionally, the precursor includes Mn2O3, Li2CO3, LiF, LiOH, Nb2O5, and / or NbF5. The annealing step can be performed under an argon gas flow. The annealing step can be performed in a temperature range of 750°C to 900°C for 6 hours or more and 24 hours or less. Optionally, the spray drying step forms secondary particles having a spherical shape.
[0041] Optionally, the irregular rock salt-type powder has the formula (i): Li x N y M z O 2-a F a (i) represented by, where 1.0 < x < 1.65; 0.01 < y < 0.55; 0.1 < z < 1; 0 ≤ a ≤ 0.5; N is one of Ti, Ta, Zr, W, Nb, or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb. Optionally, a > 0.
[0042] Optionally, the method further comprises milling the irregular rock-salt type powder with one or more carbon precursors after the annealing step. The irregular rock-salt type powder can be milled with one or more carbon precursors in a ratio where the irregular rock-salt type powder represents a majority portion and the one or more carbon precursors represent a minority portion. Optionally, the method further comprises mixing the irregular rock-salt type powder with one or more solvents to form a slurry, depositing the slurry onto a metal current collector, and drying the slurry on the metal current collector to form a composite cathode film.
[0043] In one embodiment, a cathode for a rechargeable battery includes an irregular rock salt type powder characterized by secondary particles having an average particle size of 1 micrometer or more and 20 micrometers or less. Each of the secondary particles is an agglomerate of primary particles. The primary particles have an average particle size of 400 nanometers or less.
[0044] Optionally, the secondary particles are spherical in shape. The secondary particles may have a carbon coating. The particle size of the secondary particles may be 10 micrometers or less.
[0045] In an embodiment, a method for forming a lithium ion battery includes milling a suspension of precursors to form a mixture of primary particles in the suspension. The precursors include one or more metal compounds. The method includes, after the milling step, spray drying the suspension to form secondary particles. The secondary particles are aggregates of the primary particles. The method includes annealing the secondary particles to form an irregular rock-salt type powder, and, after the annealing step, milling the irregular rock-salt type powder with one or more carbon precursors. The method further includes mixing the irregular rock-salt type powder with one or more solvents to form a slurry, drying the slurry on a metal current collector to form a composite cathode membrane, inserting the composite cathode membrane into a cell casing such that a separator is disposed between the composite cathode membrane and the anode, and providing an electrolyte into the cell casing.
[0046] The electrolyte includes a lithium salt present in a concentration suitable to conduct lithium ions through the electrolyte between the composite cathode membrane and the anode. The spray drying process can form the secondary particles to have an average particle size of 1 micrometer or more and 20 micrometers or less.
[0047] As used herein, value modifiers inserted before a numerical value, such as "about," "substantially," and "approximately," mean that the value can represent other values within a specified threshold range that are greater than and / or less than the specified value, for example values within 5%, 10%, or 15% of the specified value.
[0048] It is understood that the above description is intended to be illustrative and not restrictive. For example, the above described embodiments (and / or aspects thereof) can be used in combination with each other. In addition, many modifications can be made to adapt a particular situation or material to the teachings of the various embodiments of the present disclosure without departing from their scope. The dimensions and types of materials described herein are intended to define the parameters of the various embodiments of the present disclosure, but the embodiments are by no means limiting, but are exemplary embodiments. Many other embodiments will be apparent to those skilled in the art upon reading the above description. Thus, the scope of the various embodiments of the present disclosure should be determined with reference to the appended claims, along with the full scope of equivalents to which such claims are entitled. In the appended claims and in the detailed description herein, the terms "including" and "in which" are used as the plain English equivalents of the respective terms "comprising" and "wherein." Moreover, the terms "first," "second," and "third," etc., are used merely as labels and are not intended to impose numerical requirements on their objects. Moreover, the limitations of the following claims are not written in means-plus-function form and are not intended to be interpreted under 35 U.S.C. 112(f), unless the claim limitations specifically use the "means for" phrase prior to a recitation of a function lacking further structure.
[0049] This written specification uses examples to disclose various embodiments of the present disclosure, including the best mode, and also enables any person skilled in the art to practice various embodiments of the present disclosure, including making and using any device or system to practice any incorporated method. The patentable scope of the various embodiments of the present disclosure is defined by the claims, and may include other examples that occur to those skilled in the art. Such other examples are intended to be within the scope of the claims if they have structural elements that do not differ from the literal words of the claims, or if they include equivalent structural elements that have no substantial difference from the literal words of the claims. The present invention can be embodied in the following manner. (Appendix 1) 1. A method for forming a cathode, comprising: milling a suspension of precursors with a micromedia mill to form a mixture of primary particles in said suspension, said precursors comprising one or more metal compounds; After the grinding step, spray drying the suspension to form secondary particles, the secondary particles being agglomerates of the primary particles; and Annealing the secondary particles to form an irregular rock salt type powder. A method comprising: (Appendix 2) 2. The method of claim 1, wherein the spray drying process forms the secondary particles to have an average particle size of greater than or equal to 1 micrometer and less than or equal to 20 micrometers. (Appendix 3) 2. The method of claim 1, wherein the milling step forms a mixture of the primary particles such that the primary particles have an average particle size of 400 nanometers or less. (Appendix 4) 2. The method of claim 1, wherein the precursor comprises one or more of Mn2O3, Li2CO3, LiF, LiOH, Nb2O5, or NbF5. (Appendix 5) 2. The method of claim 1, wherein the annealing step is performed under a flow of argon gas. (Appendix 6) The method according to appended claim 1, wherein the annealing step is carried out at a temperature of 750°C to 900°C for a time of 6 hours or more and 24 hours or less. (Appended claim 7) The irregular rock salt type powder is represented by the formula (i): Li x N y M z O 2-a F a (i) wherein 1.0 < x < 1.65; 0.01 < y < 0.55; 0.1 < z < 1; 0 ≤ a < 0.5; N is one of Ti, Ta, Zr, W, Nb or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh or Sb, the method according to appended claim 1. (Appended claim 8) The method according to appended claim 1, wherein the spray drying step forms the secondary particles in a spherical shape. (Appended claim 9) The method according to appended claim 1, further comprising a step of grinding the irregular rock salt type powder together with one or more carbon precursors after the annealing step. (Appended claim 10) The method according to appended claim 9, wherein the irregular rock salt type powder is ground together with the one or more carbon precursors in a ratio such that the irregular rock salt type powder corresponds to a majority and the one or more carbon precursors correspond to a minority. (Appended claim 11) A step of mixing the irregular rock salt type powder with one or more solvents to form a slurry; A step of depositing the slurry on a metal current collector; and A step of drying the slurry on the metal current collector to form a composite cathode film, the method according to appended claim 1. (Appended claim 12) A cathode for a rechargeable battery, comprising irregular rock salt-type powder characterized by secondary particles having an average particle size of 1 micrometer or more and 20 micrometers or less, wherein each of the secondary particles is an aggregate of primary particles, and the primary particles have an average particle size of 400 nanometers or less. (Appendix 13) The irregular rock salt-type powder is represented by formula (i): Li x N y M z O 2-a F a (i) wherein 1.0 < x < 1.65; 0.01 < y < 0.55; 0.1 < z < 1; 0 ≦ a < 0.5; N is one of Ti, Ta, Zr, W, Nb or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh or Sb. The cathode according to Appendix 12. (Appendix 14) The secondary particles are spherical in shape. The cathode according to Appendix 12. (Appendix 15) a > 0. The cathode according to Appendix 12. (Appendix 16) The secondary particles have a carbon coating. The cathode according to Appendix 12. (Appendix 17) The average particle size of the secondary particles is 10 micrometers or less. The cathode according to Appendix 12. (Appendix 18) A method for forming a lithium-ion battery, comprising: a step of pulverizing a suspension of a precursor to form a mixture of primary particles in the suspension, wherein the precursor contains one or more metal compounds; a pulverization step; after the pulverization step, a step of spray-drying the suspension to form secondary particles, wherein the secondary particles are aggregates of the primary particles; a spray-drying step; a step of annealing the secondary particles to form an irregular rock salt-type powder; an annealing step; milling the irregular rock-salt type powder with one or more carbon precursors after the annealing step; mixing the irregular rock salt type powder with one or more solvents to form a slurry; drying the slurry on a metal current collector to form a composite cathode film; inserting the composite cathode membrane into a cell casing such that a separator is disposed between the composite cathode membrane and an anode; and supplying an electrolyte into the cell casing; A method comprising: (Appendix 19) 19. The method of claim 18, wherein the electrolyte comprises a lithium salt present in a concentration suitable to conduct lithium ions through the electrolyte between the composite cathode membrane and the anode. (Appendix 20) 19. The method of claim 18, wherein the spray drying process forms the secondary particles to have an average particle size of greater than or equal to 1 micrometer and less than or equal to 20 micrometers.
Claims
1. 1. A method for forming a cathode, comprising: milling a suspension of precursors with a micromedia mill to form a mixture of primary particles in said suspension, said precursors comprising one or more metal compounds; after the grinding step, spray drying the suspension to form secondary particles, the secondary particles being agglomerates of the primary particles; annealing the secondary particles to form an irregular rock-salt type powder; and milling the irregular rock-salt type powder with one or more carbon precursors after the annealing step. A method comprising:
2. 10. The method of claim 1, wherein the spray drying process forms the secondary particles to have an average particle size of 1 micrometer or more and 20 micrometers or less.
3. 10. The method of claim 1, wherein the milling step forms a mixture of the primary particles such that the primary particles have an average particle size of 400 nanometers or less.
4. The precursor is Mn 2 O 3 , Li 2 CO 3 , LiF, LiOH, Nb 2 O 5 or NbF 5 The method of claim 1 , comprising one or more of:
5. The method of claim 1 , wherein the annealing step is performed under flowing argon gas.
6. 2. The method of claim 1, wherein the annealing step is performed at a temperature between 750° C. and 900° C. for a time period of at least 6 hours and no more than 24 hours.
7. The irregular rock salt type powder has the formula (i): Li x N y M z O 2-a F a (i) 2. The method of claim 1 , wherein: 1.0<x<1.65; 0.01<y<0.55; 0.1<z<1; 0≦a<0.5; N is one of Ti, Ta, Zr, W, Nb, or Mo; and M is one of Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Al, Zr, Y, Mo, Ru, Rh, or Sb.
8. The method of claim 1 , wherein the spray drying process forms the secondary particles to be spherical in shape.
9. 10. The method of claim 1, wherein the carbon precursor comprises one or more of acetylene black, carbon black, carbon fiber, graphite, and carbon nanotubes.
10. 10. The method of claim 9, wherein the irregular rock-salt type powder is milled with the one or more carbon precursors in a ratio in which the irregular rock-salt type powder represents a majority portion and the one or more carbon precursors represent a minority portion.
11. mixing the irregular rock salt type powder with one or more solvents to form a slurry; depositing the slurry onto a metal current collector; and The method of claim 1 , further comprising drying the slurry on the metal current collector to form a composite cathode film.
Citation Information
Patent Citations
Li(NiCoMn)O2 positive electrode material, and preparation method and application thereof
CN109987650A
Method for preparing cationic unordered rock salt structure anode material through high-valent-state transition metal ion replacement combination strategies
CN110372039A
IV-VI-VIII group lithium-rich disordered rock salt structure positive electrode material and preparation method thereof
CN111211319A
Method for manufacturing positive electrode active material for lithium ion secondary battery
JP2018129140A
Cationic disordered oxides for rechargeable lithium batteries and other applications
JP2018535904A